Analysis of physical and thermodynamic properties of poly(2-cyclopentyliden-1,3-dioxolan-4-ylmethylmethacrylateco-styrene) (CPDMMA-ST) polymer using inverse gas chromatography - Hamdi Karagöz, M.; Kalkan, Adnan; Ilter, Zülfiye (Chemical Publishing Co., 2015)
In this study, thermodynamic and physical properties of poly(2-cyclopentyliden-1,3-dioxolane-4-yl-methylmethacrylate-co-styrene) (%55CPDMMA-%45ST) were investigated using inverse gas chromatography. Two groups of alcohols and alkanes with different chemical natures and polarities were used to determine certain properties of (CPDMMA-ST)-solute systems. The specific retention volume (Vg0), glass transition temperature (Tg), adsorption enthalpy (?Ha), the sorption enthalpy (?H1S), sorption free energy (?G1S), sorption entropy (?S1S), weight fraction activity coefficients of solute probes at infinite dilution (?1?), partial molar enthalpy of solute probes at infinite dilution (?H1?) and Flory-Huggins interaction parameters (?12?), between polymer and solvents were determined in the temperature range of 313-473 K. In addition, the solubility parameters of CPDMMA-ST at infinite dilution was determined by plotting the graph of [?12-(?G1?/V1)] versus solubility parameters (?1), of probes.
Keywords: Inverse gas chromatography; Poly(2-cyclopentyliden-1,3-dioxolan-4-yl-methylmethacrylate-co-styrene); Polymer